Differential pricing of pharmaceuticals: a bibliometric review of the literature. Issue 3 (30th July 2014) - Babar, Zaheer‐Ud‐Din; Atif, Muhammad
Abstract Objectives The objective of this study was to perform a bibliometric review of the literature related to differential pricing of pharmaceuticals. Methods A bibliometric literature review was performed with a particular focus on 'differential pricing and medicines'. Six hundred and thirty relevant articles were found, and 56 studies and documents matched the criteria for further screening. Thirty‐eight articles were included in the final analysis. Key findings The literature suggests that there are conflicting views regarding differential pricing. It has been difficult to implement differential pricing for medicines, and it has not been tried for most of the medicines. However, for products such as vaccines, drugs for human immunodeficiency virus/acquired immunodeficiency syndrome, malaria and tuberculosis, differential pricing has been applied resulting in improved access to medicines. Also, there are questions as to how fair and affordable the differential prices are, and more research is needed regarding internal market segmentation and private and public distribution channels. Differential pricing is only feasible for 'global' diseases, whereby drugs have a rich country market to recoup research and development costs – there is no solution for 'neglected' diseases. Also, differential prices rely on pharmaceutical industry, and it does not encourage sustainability or autonomy in developing countries. Conclusion Differential pricing is not a panacea for all pricing issues, but it should be recognised as one of the solutions to improve the access to medicines worldwide. Further research is required regarding how a systematic differential pricing scheme, inclusive of all countries and all pharmaceuticals, can be achieved.